Do women with venous thromboembolism bleed more than men during anticoagulation? Data from the real-life, prospective START-Register. (December 2021) - Palareti, Gualtiero; Legnani, Cristina; Antonucci, Emilia; Cosmi, Benilde; Falanga, Anna; Poli, Daniela; Mastroiacovo, Daniela; Pengo, Vittorio; Ageno, Walter; Testa, Sophie
Background: Venous thromboembolism (VTE) is a frequent and serious disease that requires immediate and long-term anticoagulant treatment, which is inevitably associated with a risk of bleeding complications. Some studies, though not all, reported a higher risk of bleeding in female patients treated with either old anticoagulants [vitamin k antagonists (VKAs)] or recent anticoagulants [direct oral anticoagulants (DOACs)]. Furthermore, analyses of clinical trials reported an abnormal vaginal bleeding in women of reproductive age treated with DOACs. This study aimed at comparing the risk of bleeding in an inception cohort of VTE women and men included in a prospective observational registry. Methods: Baseline characteristics and bleeding events occurring during anticoagulation in patients of both sexes, included in the START-Register after a first VTE, were analyzed. Results: In all, 1298 women were compared with 1290 men. Women were older and more often had renal diseases; their index events were often provoked (often by hormonal contraception and pregnancy), and more frequently presented as isolated pulmonary embolism (PE). The rate of bleeding was similar in women (2.9% patient-years) and men (2.1% patient-years), though it was higher when uterine bleeds were included (3.5% patient-years, p = 0.0141). More bleeds occurred in VKA- than DOAC-treated patients (6.4% versus 2.6%, respectively; p = 0.0013). At multivariate analysis, age ⩾ 75 years was associated with higher prevalence of bleeds. Conclusion: The occurrence of bleeding was not different between women and men during anticoagulation after VTE. Only after inclusion of vaginal/uterine bleeds, the rate of bleeding was higher in women. The incidence of bleeding was higher in women treated with VKAs. Plain Language Summary: The risk of bleeding in women anticoagulated for deep vein thrombosis or pulmonary embolism is not higher than that in men, except for vaginal bleeding: Background: The occurrence of a venous thromboembolic event (VTE, including deep vein thrombosis and pulmonary embolism) necessarily requires a period of at least 3–6 months of treatment with anticoagulant drugs [either vitamin k antagonists (VKA) or, more recently, direct oral anticoagulants (DOACs)]. Anticoagulation therapy, however, is associated with a risk of bleeding that is influenced by several factors. Sex is one of these factors as some authors have hypothesized that women are at higher risk than men. Furthermore, some studies have recently found more vaginal bleeding in VTE women treated with a DOAC compared with those who received VKAs. Methods: The present study aimed to compare the frequency of bleeds occurring in women and in men who were treated with DOACs or VKAs for a first VTE event and followed in real-life conditions. Since the beginning of their anticoagulant treatment, the patients were included in a prospective, multicenter, observational registry (the START-Register), and bleeding events were recorded. Results: A total of 1298 women were compared with 1290 men. Women were older and more often were affected by renal diseases; their VTE events were often associated with risk factors (especially hormonal contraception and pregnancy) and presented as isolated pulmonary embolism. The rate of all bleeding events (including major, non-major but clinically relevant, and minor bleeds) was higher in women (3.5% patient-years) than in men (2.1% patient-years, p = 0.0141); however, the difference was no longer statistically significant after exclusion of uterine bleeds (2.9% patient years). More bleeding occurred in women receiving VKA as anticoagulant drug compared with those treated with a DOAC (6.4% versus 2.6%, respectively; p = 0.0013). At multivariate analysis, age ⩾ 75 years was associated with higher prevalence of bleeds. Conclusion: In conclusion, we found that in real-life conditions, the rate of bleeding events occurring during anticoagulation after a VTE episode is not higher in women than in men. Only after inclusion of vaginal bleeds, the rate of bleeding was higher in women. More bleeds (including vaginal bleeding) occurred in women treated with VKA than DOACs.